2005
DOI: 10.1677/erc.1.00950
|View full text |Cite
|
Sign up to set email alerts
|

Cellular prostatic acid phosphatase: a protein tyrosine phosphatase involved in androgen-independent proliferation of prostate cancer

Abstract: Human prostatic acid phosphatase (PAcP) was used as a valuable surrogate marker for monitoring prostate cancer prior to the availability of prostate-specific antigen (PSA). Even though the level of PAcP is increased in the circulation of prostate cancer patients, its intracellular level and activity are greatly diminished in prostate cancer cells. Recent advances in understanding the function of the cellular form of PAcP (cPAcP) have shed some light on its role in prostate carcinogenesis, which may have potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 106 publications
(83 reference statements)
4
109
0
3
Order By: Relevance
“…Additionally, EGF or heregulin had no effect on promoting the adhesive ability of C-33 cells (Supplementary Figure 4). We propose that in androgenindependent, AR-positive PCa cells, ErbB-2 protein is constitutively activated and/or elevated as seen in clinical samples due, in part, to the loss or null of cPAcP expression (Signoretti et al, 2000;Veeramani et al, 2005). In those advanced PCa cells, signal pathways initiated by highly activated ErbB-2 lead to a sustained activation of PYK2 and PYK2-mediated functions, which differs from the transient effect activated by ErbB ligands (Zrihan-Licht et al, 2000;van der Horst et al, 2005;Park et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, EGF or heregulin had no effect on promoting the adhesive ability of C-33 cells (Supplementary Figure 4). We propose that in androgenindependent, AR-positive PCa cells, ErbB-2 protein is constitutively activated and/or elevated as seen in clinical samples due, in part, to the loss or null of cPAcP expression (Signoretti et al, 2000;Veeramani et al, 2005). In those advanced PCa cells, signal pathways initiated by highly activated ErbB-2 lead to a sustained activation of PYK2 and PYK2-mediated functions, which differs from the transient effect activated by ErbB ligands (Zrihan-Licht et al, 2000;van der Horst et al, 2005;Park et al, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Preliminary data showed that in PAcP siRNA oligomertransfected cells, tyrosyl phosphorylation of ErbB-2 and PYK2 increased, higher than that in the scrambled control siRNA oligomer-transfected cells (Veeramani et al, 2005). We established PAcP-knockdown stable subclones in C-33 cells and analysed their adhesion.…”
Section: Role Of Erbb-2 In Regulating the Pyk2 Activity And The Adhesmentioning
confidence: 98%
See 1 more Smart Citation
“…PAP๋Š” PSA์™€ ๊ฐ™์€ ๋‹ค๋ฅธ ์ „๋ฆฝ์„  ์•” ํ‘œ์ง€์ž๋“ค๋ณด๋‹ค ํ˜•ํƒœํ•™์  ํŠน์ง•๊ณผ ๋†’์€ ์ƒ๊ด€๊ด€๊ณ„๋ฅผ ์ง€๋‹ˆ๊ณ  ์žˆ๊ธฐ ๋•Œ๋ฌธ์— [9], ์ด๋ฅผ ๋ฐ”ํƒ•์œผ ๋กœ PAP๋Š” ๊ณผ๊ฑฐ ์ˆ˜์‹ญ๋…„๊ฐ„ ์ „๋ฆฝ์„  ์•”์˜ ํ‘œ์ง€์ž(marker)๋กœ์„œ ํ˜ˆ ์ฒญ๊ฒ€์‚ฌ์™€ ์กฐ์ง๊ฒ€์‚ฌ์— ๋„๋ฆฌ ์‚ฌ์šฉ๋˜์–ด ์™”๋‹ค. ์ด๋Ÿฐ ํ‘œ์ง€์ž๋กœ์„œ์˜ ๊ธฐ๋Šฅ๊ณผ๋Š” ๋‹ค๋ฅธ ์ธก๋ฉด์œผ๋กœ ์ „๋ฆฝ์„ ์ด ์•”์ด ๋˜๋Š” ๊ณผ์ •์—์„œ cellular PAP ๋ฐœํ˜„์˜ ๊ฐ์†Œ๋กœ ์ธํ•ด ํƒˆ ์ธ์‚ฐํ™”๊ฐ€ ์ œ๋Œ€๋กœ ์ผ์–ด๋‚˜์ง€ ์•Š์•„ ์„ธํฌ ์„ฑ์žฅ ์‹ ํ˜ธ๊ฐ€ ์ง€์†์ ์œผ๋กœ ์œ ์ง€๋˜๋Š” ํ˜„์ƒ๋„ ๋ฐํ˜€์กŒ๋‹ค [20,22,23,38,42]. ์ฆ‰, cellular PAP ๋ฐœํ˜„์˜ ๊ฐ์†Œ๊ฐ€ ์ „๋ฆฝ์„  ์•” ๋ฐœ ์ƒ ์›์ธ์ค‘์˜ ํ•˜๋‚˜๊ฐ€ ๋˜๊ณ , ์ด ๊ฒฝ์šฐ PAP๋Š” tumor supressor์˜ ์—ญํ• ์„ ํ•˜๋Š” ๊ฒƒ์œผ๋กœ ์ถ”์ •๋œ๋‹ค [42] (Table 1).…”
unclassified
“…์ด๋Ÿฐ ํ‘œ์ง€์ž๋กœ์„œ์˜ ๊ธฐ๋Šฅ๊ณผ๋Š” ๋‹ค๋ฅธ ์ธก๋ฉด์œผ๋กœ ์ „๋ฆฝ์„ ์ด ์•”์ด ๋˜๋Š” ๊ณผ์ •์—์„œ cellular PAP ๋ฐœํ˜„์˜ ๊ฐ์†Œ๋กœ ์ธํ•ด ํƒˆ ์ธ์‚ฐํ™”๊ฐ€ ์ œ๋Œ€๋กœ ์ผ์–ด๋‚˜์ง€ ์•Š์•„ ์„ธํฌ ์„ฑ์žฅ ์‹ ํ˜ธ๊ฐ€ ์ง€์†์ ์œผ๋กœ ์œ ์ง€๋˜๋Š” ํ˜„์ƒ๋„ ๋ฐํ˜€์กŒ๋‹ค [20,22,23,38,42]. ์ฆ‰, cellular PAP ๋ฐœํ˜„์˜ ๊ฐ์†Œ๊ฐ€ ์ „๋ฆฝ์„  ์•” ๋ฐœ ์ƒ ์›์ธ์ค‘์˜ ํ•˜๋‚˜๊ฐ€ ๋˜๊ณ , ์ด ๊ฒฝ์šฐ PAP๋Š” tumor supressor์˜ ์—ญํ• ์„ ํ•˜๋Š” ๊ฒƒ์œผ๋กœ ์ถ”์ •๋œ๋‹ค [42] (Table 1). PAP์˜ ์ „๋ฆฝ์„  ํŠน ์ด์  ๋ฐœํ˜„์˜ ์กฐ์ ˆ ๊ธฐ์ž‘ ๊ด€๋ จํ•ด์„œ๋„ PAP promoter ๋ถ€์œ„์—์„œ์˜ cis-acting element๋“ค์ด ๋ช‡๋ช‡ ๋ณด๊ณ ๋œ ๋ฐ” ์žˆ์ง€๋งŒ [27,29,33,34,50] (Fig.…”
unclassified